Histopathological evaluation of nail lichen planus: A cross‐sectional study. (22nd September 2020) - Kharghoria, Geetali; Grover, Chander; Bhattacharya, Sambit Nath; Sharma, Sonal
Abstract: Introduction: Up to 10% of patients with lichen planus (LP) have nail involvement; still there is a paucity of studies on histopathological features. Nevertheless, nail biopsy is the diagnostic standard, especially for isolated nail LP. Methodology: Nails of 45 patients with nail LP were evaluated clinically and biopsies taken from most involved nail (25 nail bed and 20 matrix biopsies). Correlation of clinical and histopathological features was also done. Results: The mean age of the study group participants was 36.91 ± 18.27 years with a M:F ratio of 1.81:1. The most common clinical variant of LP seen was oral LP (51%), with isolated nail involvement in 29%. Clinically, major features were onychorrhexis (92.3%), longitudinal melanonychia (74.3%), and nail bed erythema (54%). Histopathologically, hypergranulosis of nail matrix and bed epithelium (51.1%), followed by sawtooth acanthosis (44.4%) and lichenoid band (24.4%) were most common. A diagnosis using prevalent diagnostic criteria was confirmed in 51.1% biopsies. Distinctive "fraying of nail plate, " a change not previously described, was noted in 33.3% cases. Conclusion: Histopathology of nail LP has been attributed a diagnostic role; however, existing diagnostic criteria are not sensitive enough and need refinement. Not hitherto described features like fraying of nail plate are seen in a significant number of cases.